PERENCANAAN KOLAM RETENSI DAN STASIUN POMPA PADA SISTEM DRAINASE KALI SEMARANG - Muhammad Dwi Prayoga; Rizky Tegar Wicaksono Agami; Sri Sangkawati; Sugiyanto Sugiyanto (Jurnal Karya Teknik Sipil, 2013)
Drainage system with retention pond and pumping station is the most effective and efficient system to manage flood in drainage area. Semarang River catchment area has became one of important area in Semarang, because it ends near Tanjung Mas Port, that is basically one of central business district in Semarang, so that the flood which inundate that area become major problem for local government. Retention pond and pumping station drainage system are designed using 10 year return period flood discharge. From the result of 10 year recurrence interval rainfall data processing by using Nakyasu method, thus can be obtained Q design = 63,983 m3/sec, that  will be used to design drainage channel. By comparing existing drainage channel and designed drainage channel, it’s obtained that drainage channel in M.H. Thamrin Street and Gajah Mada Street need to be replaced, because they can’t intercept and retain flood discharge. By using flood routing method with 10 year recurrence interval Q, it can be obtained the area of retention pond  is 68.000m2 and 88.400m3 with  8  pumps in total with 5 m3/sec capacity for each pump.